Postmaterialism and corporate tax avoidance - CUI, Yujia (Institutional Knowledge at Singapore Management University, 2022)
This paper explores how postmaterialism culture influences corporate tax avoidance behavior. Using a proprietary dataset of China tax audits, we find that firms owned by investors from countries with higher postmaterialism values are less likely to engage in tax avoidance behavior in China. In addition, we find some evidence that the negative association between postmaterialism and tax avoidance is more pronounced when tax enforcement is stronger, indicating that national culture and formal institutions act as complements. To check the external validity of our main results, we further use a cross-country sample from 21 countries over 22 years. The evidence from the cross-country sample is consistent with the findings obtained from the China tax audits setting.